Artificial intelligence literacy among hospital administrative staff: a qualitative descriptive study - Gökhan Coşkun; Yeliz Cankurtaran (BMC Health Services Research, 2026)
Abstract Background Artificial intelligence (AI) is increasingly being integrated into healthcare organizations, creating a growing need for AI literacy among healthcare personnel. However, the AI literacy of hospital administrative staff remains relatively underexplored. This study examines the level and perceptions of AI literacy among hospital administrative staff and explores participants’ views regarding AI literacy. Methods This qualitative descriptive study was conducted with 20 administrative staff members at Amasya Sabuncuoğlu Şerefeddin Training and Research Hospital in Türkiye. Data were collected through semi-structured interviews and analyzed using thematic analysis. Results Participants generally defined AI literacy in terms of basic awareness, simple operational skills, and the ability to use AI applications appropriately. AI technologies were mainly perceived as tools that enable rapid access to information, support decision-making, provide comprehensive information, broaden perspectives, simplify administrative tasks, and assist planning. Despite these perceived benefits, many participants reported not actively using AI-based applications in their institutions. Current reported use was largely limited to decision-support systems and the Central Physician Appointment System (MHRS), which some participants identified as an AI-supported application. Participants’ views on challenges revealed a contrast between those reporting no difficulties and those acknowledging limited knowledge and insufficient institutional guidance. Conclusions The findings indicate that AI literacy among hospital administrative staff remains largely at a basic and operational level, with limited integration into strategic decision-making processes. The findings highlight the need for structured training programs, organizational strategies, and policy frameworks to strengthen AI literacy and support the effective integration of AI into healthcare administration.